Two isostructural Co(II) flufenamato and niflumato complexes with bathocuproine: Analogues with a different cytotoxic activity - Smolko, Lukáš; Smolková, Romana; Samoľová, Erika; Morgan, Ibrahim; Saoud, Mohamad; Kaluđerović, Goran N (Journal of inorganic biochemistry, 2020)
Two novel Co(II) fenamato complexes containing bathocuproine (bcp), namely [Co(bcp)(flu)2] (1) and [Co(bcp)(nif)2] (2) (flu = flufenamato, nif = niflumato) were synthesized and characterized by elemental analysis, single-crystal X-ray structure analysis as well as absorption and fluorescence spectroscopy. Investigation of their molecular structure revealed that both complexes are isostructural and form analogous complex molecules, with a Co(II) atom hexacoordinated by two nitrogen atoms of bcp and four oxygen atoms of two chelate bonded flu (1) and nif (2) ligands in a distorted octahedral arrangement. Surprisingly, the results of cytotoxicity experiments on four cancer cell lines (HeLa, HT-29, PC-3 and MCF-7) have revealed that despite similar structure of the complexes, the nif complex exhibits significantly higher activity, being the most effective against the PC-3 cell line (IC50 (MTT) = 6.11 ± 1.95 μM). Further studies performed on PC-3 cell line have shown that the mechanism of the cytotoxic action of nif complex (2) might involve activation of autophagic processes and apoptosis, while for its flu analogue (1) apoptosis was detected.
Keywords: Flufenamic Acid; apoptóza; kyselina flufenamová; Autophagy; Cell Line, Tumor; kobalt; G1 Phase Cell Cycle Checkpoints; Apoptosis; screeningové testy protinádorových léčiv; Molecular Structure; nádorové buněčné linie; Structure-Activity Relationship; lidé; Antineoplastic Agents; protinádorové látky; komplexní sloučeniny; Phenanthrolines; Ligands; Coordination Complexes; autofagie; molekulární struktura; kontrolní body fáze G1 buněčného cyklu; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; fenantroliny; Cobalt; ligandy; Humans